Diffractive dijet production in (p)over-barp collisions at root s=1.96 TeV - Aaltonen, T; Albrow, M; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; et al. (2012)
We report on a study of diffractive dijet production in p̄p collisions at √s=1.96TeV using the CDF II detector at the Fermilab Tevatron p̄p collider. A data sample from 310pb -1 of integrated luminosity collected by triggering on a high transverse energy jet, ETjet, in coincidence with a recoil antiproton detected in a Roman pot spectrometer is used to measure the ratio of single-diffractive to inclusive-dijet event rates as a function of xp ̄ of the interacting parton in the antiproton, the Bjorken-x, xBjp̄, and a Q2(ETjet)2 in the ranges 10 -3<xbjp̄<10 -1="" 0.03<ξ="" 102<q2<104gev2,="" a="" and="" are="" for="" four-momentum="" fraction="" of="" presented="" p̄="" p̄-momentum-loss="" p̄<0.09="" region="" respectively.="" results="" squared="" t="" the="" transfer="">-4GeV2. The t p̄ dependence is measured as a function of Q2 and xBjp̄ and compared with that of inclusive single diffraction dissociation. We find weak xBjp̄ and Q2 dependencies in the ratio of single diffractive to inclusive event rates, and no significant Q2 dependence in the diffractive t p̄ distributions. © 2012 American Physical Society.</xbjp̄<10>